Development of Project Based Learning Modules On Materials Static Fluids for Class of XI Senior High School - Fatia Nurul Asma; Fitriyawany Fitriyawany; Cut Rizki Mustika (Asian Journal of Science Education, 2022)
One of the factors that affect the quality of education is the lack of availability of teaching materials. Based on observations that have been made, it was found that the teaching materials used in learning were worksheets and textbooks, there was no use of laboratories, the lack of active role of students in learning, and material that was difficult for them to understand contained static fluids, especially in an enclosed space. This research and development aim to see the design and also feasibility level of the module from the perspective of media experts and material experts. The method used is research and development (RD) concerning the 4D model with 4 stages, namely define, design, development, and disseminate. The subjects in this study were media design experts and material experts. The instrument used in this study was a validation questionnaire given to media experts and material experts. Validation questionnaire related to the suitability of the material and the suitability of the design of the product being developed. Data from the instrument validation sheet were analyzed using a Likert scale. The results of the media expert validation obtained an average score of 3.825 with a feasibility percentage of 95.625% in the very feasible category, while the results of the material expert validation obtained an average score of 3.7 with a feasibility percentage of 92.5% in the very feasible category.